Birth and the magistrate: The influence of pregnancy on judicial decisions - Waits, Kristi Dawne (1998)
As the number of pregnant defendents continues to grow, so too do the problems and concerns surrounding them. While literature can be found on related topics, the specific issue of pregnancy and judicial decisions has yet to be examined. The purpose of this particular research study is to heighten awareness of the issues surrounding the topic, and provide evidence indicating the influence, if any, pregnancy has on judicial decisions